Cold seeps alter the near-bottom biogeochemistry in the ultraoligotrophic Southeastern Mediterranean Sea. (May 2022) - Sisma-Ventura, Guy; Bialik, Or M.; Makovsky, Yizhaq; Rahav, Eyal; Ozer, Tal; Kanari, Mor; Marmen, Sophi; Belkin, Natalia; Guy-Haim, Tamar; Antler, Gilad; Herut, Barak; Rubin-Blum, Maxim
Abstract: To better understand the sphere of influence of seafloor hydrocarbon seepage in an oligotrophic marine environment, we evaluated the near-bottom biogeochemistry in near-seep and control locations of the ultra-oligotrophic Southeast Mediterranean Sea. We observed corrosive pH (pHTotal at 25 °C as low as 6.83) in water overlying a seepage site. The aberrant pH values (6.8–7.4) were measured up to 50 m above the seafloor and were accompanied by anomalously variable nutrient distribution with elevated nitrate + nitrite to phosphate ratio (30:1–53:1). The dissolved inorganic carbon (DIC) from the seeps has likely reached the water column, as low pH was decoupled from changes in alkalinity. Amplicon sequencing and metagenomics suggest that the oxidation of methane to CO2 in the deep water is catalyzed by aerobic methane-oxidizing bacteria, which were prominent below 800 m depth. Incubation experiments suggest that gas seepage affected the sediment-water nutrient exchange. Oxygen consumption rates in bioturbated sediments near the seeps were three times above the background, the influx of NO 3 − and NH 4 +, was substantial, and we detected an early diagenetic loss of PO 4 3 − . The low δ 13 C values of particulate organic matter (-29.0 and -25.0‰), and its high C:N ratio (11.78–16.76) indicate that the seeps affect the suspended particles in the overlying water, and thus may influence the trophic webs. We show that the seeps affect the functionality of the deep-sea environment, being an important source of carbon and altering nutrient regimes in oligotrophic regions. Highlights: Gas seeps potentially affect the functionality of the deep oligotrophic Southeastern Mediterranean Sea. Corrosive pH as low as 6.83 and elevated N to P ratio of 30:1–53:1 in water overlying a seepage site. Bioturbated sediments near the Palmahim Disturbance seeps catalyze rapid nutrient cycling. High microbial activity and changes in microbial communities near the seabed. Potential C and N export from Palmahim Disturbance seeps.